Sosialisasi Permainan Bola Voli Bagi Anak Desa Pasar Seluma Kabupaten Seluma - Sucipto, Jhulius Afrilian (Jurnal Kewirausahaan dan Bisnis, 2024)
Community service that aims to provide socialization of volleyball games to children in Pasar Seluma Village, Seluma Regency. The main focus of this service is to make a positive contribution to the physical, social, and skill development of the children through introduction and training in the game of volleyball. This service began with a needs analysis of the local community and identification of potential development through the game of volleyball. Collaboration with local stakeholders, such as community leaders, teachers, and parents, formed the basis of planning that was participatory and responsive to the cultural context and specific needs of the village. The service approach involved a series of activities, including socialization, training, and matches. The service team consisted of experienced volleyball coaches and local facilitators whose role was to provide basic knowledge of the sport. In addition to the technical aspects of the game, empowering children through a learning approach that involves values such as cooperation, sportsmanship, and leadership was also a major focus. Evaluation was conducted through monitoring children's participation, measuring changes in skills, as well as feedback from participants and stakeholders. The results of this evaluation helped assess the positive impacts and constraints that arose during the implementation of the community service program. The results of this study not only provide an in-depth understanding of the effectiveness of the volleyball socialization program at the community level, but also offer recommendations for further development and increased sustainability. The conclusions of this service can serve as a foundation for similar projects in other areas, emphasizing the importance of actively involving the community in efforts to develop and coach children through sports.